Case Study: CGIAR investment in innovation for sustainable agricultural intensification - Dalberg Asia (Commission on Sustainable Agriculture Intensification, 2021)
The CGIAR is the leading global agriculture research institution working towards creating sustainable agricultural practices a reality through research and innovation. The CGIAR 2030 Research and Innovation Strategy states that the “CGIAR will contribute to collective global targets for transformation of food, land, and water systems across local, regional, and global levels. In action, CGIAR plays a unique role in forming global research partnerships to work directly with national agricultural research systems to research and develop technologies to address challenges in agriculture.